2019
DOI: 10.1016/j.seizure.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of low cost epilepsy surgery centers in resource poor setting

Abstract: To prospectively assess the feasibility of establishing low cost epilepsy surgery programs in resource poor settings. Method: We started epilepsy surgery centers in Tier 2 and Tier 3 cities in India in private hospitals. This model is based on the identifying and operating ideal epilepsy surgery candidates on the basis of clinical history, interictal and ictal video-EEG data, and 1.5 T MRI without other investigations and without regular involvement of other specialists. Trained epileptologists formed the fulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…A single epilepsy center may already have a large impact in small countries such as Georgia [26], but for large countries such as India or China, a multi-tiered sys-tem of epilepsy centers with different levels of expertise is advisable [16,19,32,116]. At the most basic level, specially trained physicians would treat and care for patients with epilepsy according to standard protocols, simple centers could perform temporal lobectomy according to standardized protocols for diagnosis, assessment, and surgery, while comprehensive epilepsy surgery centers are needed for further diagnostics and more complex surgical scenarios.…”
Section: Use a Multi-tiered System To Reach Areas Outside The Large C...mentioning
confidence: 99%
See 1 more Smart Citation
“…A single epilepsy center may already have a large impact in small countries such as Georgia [26], but for large countries such as India or China, a multi-tiered sys-tem of epilepsy centers with different levels of expertise is advisable [16,19,32,116]. At the most basic level, specially trained physicians would treat and care for patients with epilepsy according to standard protocols, simple centers could perform temporal lobectomy according to standardized protocols for diagnosis, assessment, and surgery, while comprehensive epilepsy surgery centers are needed for further diagnostics and more complex surgical scenarios.…”
Section: Use a Multi-tiered System To Reach Areas Outside The Large C...mentioning
confidence: 99%
“…A recent survey for Africa [11] found that epilepsy surgery is performed in only 8 out of 51 countries, with only one country reporting invasive presurgical diagnostics. As a consequence, clear-cut cases with excellent outcome prognosis, such as patients with mesial temporal lobe epilepsy (MTLE) with hippocampal sclerosis (HS), accumulate in LMIC [12][13][14], even though the establishment of low-cost epilepsy surgery programs is feasible in countries with resource-poor settings [15,16]. Furthermore, with a rapidly growing population in LMIC, the gap between the number of patients who could benefit from surgical intervention and those who can actually receive it is widening yearly [11], making the initiation of surgical epilepsy services for those countries a timely issue.…”
Section: Introductionmentioning
confidence: 99%
“…
I read with interest the article by Jukkarwala et al entitled: "Establishment of low cost epilepsy surgery centers in resource poor setting" [1]. I agree with their conclusion that "It is possible to establish successful epilepsy surgery programs in resource poor setting with reasonable costs" [1]. However, I would like to suggest a strategy to reduce the costs substantially compared with their achievement of USD 1324 per patient.
…”
mentioning
confidence: 91%
“…Despite the obvious benefits of neurosurgical intervention, there is a widely recognized surgical treatment gap [14], particularly in low-and middle-income countries lacking the appropriate specialization. Consequently, MTLE patients with a clear-cut surgical recommendation and excellent outcome prognosis accumulate in these countries, even though those patients could be identified appropriately within a limited resource setting [15]. In addition, emerging economies like Argentina [16], Colombia [17], India [15,18], Lebanon [19], Panama [20] or Tunisia [21] report seizure freedom rates after surgical resection comparable to that of high-income countries [22].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MTLE patients with a clear-cut surgical recommendation and excellent outcome prognosis accumulate in these countries, even though those patients could be identified appropriately within a limited resource setting [15]. In addition, emerging economies like Argentina [16], Colombia [17], India [15,18], Lebanon [19], Panama [20] or Tunisia [21] report seizure freedom rates after surgical resection comparable to that of high-income countries [22]. Similar results can be achieved even in low-resource settings, as reported for Uganda [23].…”
Section: Introductionmentioning
confidence: 99%